Research on the Implementation Mechanism of Blended Classroom Teaching in Higher Vocational Colleges under the OBE-PBL Dual Orientation - Dou, Anqi; Li, Can (Education Insights, 2026)
With the continuous integration of information technology into vocational education, blended classroom teaching has become an important approach to instructional reform in higher vocational colleges. However, its practical implementation often faces challenges such as unclear learning objectives, fragmented teaching processes, and insufficient student engagement. To address these issues, this study explores a blended teaching model guided by the dual orientation of Outcome-Based Education (OBE) and Problem-Based Learning (PBL). Based on an analysis of the conceptual foundations of OBE and PBL, an OBE-PBL dual-oriented blended teaching implementation mechanism is constructed, consisting of outcome-driven goal alignment, problem-driven learning processes, coordinated online-offline instruction, and feedback-oriented evaluation. Through teaching practice analysis and reflective discussion in higher vocational contexts, the study examines the practical value and implementation conditions of the proposed model. The results suggest that the OBE-PBL dual-oriented framework provides a systematic and operable reference for improving the coherence and effectiveness of blended classroom teaching in higher vocational education, while also indicating directions for future optimization and empirical validation.